ANALISIS SHORROF ISIM MUSYTAQ DARI SURAT AL-QOLAM DAN ISTIFADAHNYA UNTUK PENINGKATAN MENGHAFAL MUFRODAT - Ahmad Nihami Munawwir; Burhanudin Ubaid (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research aims to analyze the morphological structure of isim musytaq in Surah Al-Qolam and its application in enhancing vocabulary memorization (mufrodat) in Arabic language learning. Isim musytaq refers to derived nouns in Arabic, playing a crucial role in vocabulary formation. This study adopts a qualitative descriptive method with linguistic and morphological approaches to the verses in Surah Al-Qolam. The analysis focuses on the form, meaning, and grammatical function of isim musytaq and its didactic values. Findings reveal that there are various isim musytaq types in the surah that serve as effective tools in teaching Arabic vocabulary. These linguistic elements can enhance students’ comprehension and mastery of Arabic language skills, particularly in reading and interpreting Qur’anic texts. The research is expected to serve as a reference for developing Qur’an-based vocabulary teaching models, especially in morphology.